Structural isomers of the S2 state in photosystem II: do they exist at room temperature and are they important for function?. Issue 1 (15th March 2019) - Chatterjee, Ruchira; Lassalle, Louise; Gul, Sheraz; Fuller, Franklin D.; Young, Iris D.; Ibrahim, Mohamed; de Lichtenberg, Casper; Cheah, Mun Hon; Zouni, Athina; Messinger, Johannes; Yachandra, Vittal K.; Kern, Jan; et al.
Abstract : In nature, an oxo‐bridged Mn4 CaO5 cluster embedded in photosystem II (PSII), a membrane‐bound multi‐subunit pigment protein complex, catalyzes the water oxidation reaction that is driven by light‐induced charge separations in the reaction center of PSII. The Mn4 CaO5 cluster accumulates four oxidizing equivalents to enable the four‐electron four‐proton catalysis of two water molecules to one dioxygen molecule and cycles through five intermediate S‐states, S0 – S4 in the Kok cycle. One important question related to the catalytic mechanism of the oxygen‐evolving complex (OEC) that remains is, whether structural isomers are present in some of the intermediate S‐states and if such equilibria are essential for the mechanism of the O‐O bond formation. Here we compare results from electron paramagnetic resonance (EPR) and X‐ray absorption spectroscopy (XAS) obtained at cryogenic temperatures for the S2 state of PSII with structural data collected of the S1, S2 and S3 states by serial crystallography at neutral pH (∼6.5) using an X‐ray free electron laser at room temperature. While the cryogenic data show the presence of at least two structural forms of the S2 state, the room temperature crystallography data can be well‐described by just one S2 structure. We discuss the deviating results and outline experimental strategies for clarifying this mechanistically important question.